2019
DOI: 10.1002/hon.2657
|View full text |Cite
|
Sign up to set email alerts
|

CD5 expression correlates with inferior survival and enhances the negative effect of p53 overexpression in diffuse large B‐cell lymphoma

Abstract: De novo CD5‐positive diffuse large B‐cell lymphoma (CD5+ DLBCL) is increasingly recognized as a distinct pathologic phenomenon with a specific clinical picture. However, CD5+ DLBCL has not been studied on a large scale in China. In this study, we show that CD5+ DLBCL occurs at a low frequency (9.2%). Comparison of clinical characteristics of CD5+ vs CD5− DLBCL showed that CD5+ DLBCL was more frequently elderly (>60 years) and had B symptoms, high‐performance status, stage III‐IV, an IPI score >2 and bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
(72 reference statements)
2
13
0
Order By: Relevance
“…For c‐MYC IHC, the UltraView™ Universal DAB Detection Kit (Ventana Medical Systems Inc., Tucson, AZ, USA) was used to increase the staining intensity. The cut‐off for c‐MYC positivity was more than 40% of tumour cells showing immunoreactivity, whereas thresholds for BCL2, p53, CD5, and CD23 were more than 50%, in accordance with previously established cut‐offs [ 31 , 33 , 37 , 38 ]. For Ki67, results were rendered semi‐quantitatively on a scale from 1 to 4+, according to the percentage of positive cells (1+ [1–25%], 2+ [26–50%], 3+ [51–75%], and 4+ [76–100%]) [ 18 ].…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…For c‐MYC IHC, the UltraView™ Universal DAB Detection Kit (Ventana Medical Systems Inc., Tucson, AZ, USA) was used to increase the staining intensity. The cut‐off for c‐MYC positivity was more than 40% of tumour cells showing immunoreactivity, whereas thresholds for BCL2, p53, CD5, and CD23 were more than 50%, in accordance with previously established cut‐offs [ 31 , 33 , 37 , 38 ]. For Ki67, results were rendered semi‐quantitatively on a scale from 1 to 4+, according to the percentage of positive cells (1+ [1–25%], 2+ [26–50%], 3+ [51–75%], and 4+ [76–100%]) [ 18 ].…”
Section: Methodssupporting
confidence: 86%
“…Moreover, some studies showed that p53 overexpression enhances c‐MYC‐related adverse effects in DLBCL, identifying a high risk of relapse subgroup of patients co‐expressing c‐MYC and p53 [ 34 , 36 ]. Other IHC biomarkers can also be used, such as CD5 and CD23, which are positive in 5–10% of DLBCL [ 37 , 38 ] but their significance still remains controversial. On one hand, CD23 is expressed on naïve B cells and follicular dendritic cells and its overexpression has been associated with unfavourable outcomes in DLBCL [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, poor prognosis was presented in cancer survivors with high expression of CA5R1 (46)(47)(48)(49). CD5 was identified as a prognostic factor in large B-cell lymphoma with increased expression correlated to inferior survival (50). However, the expression of CD86, CA5R1, and CD5 seemed to be downregulated in the high-risk group, which could be due to the uniqueness of TME in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various markers are defined through immunophenotyping, such as CD5, CD30, BCL2, MYC, and TP53 ( Pierce and Mehta, 2017 ; Zhao et al, 2019 ). CD5 promotes downstream B-cell receptor signaling, is associated with ABC subtype and more aggressive clinical traits.…”
Section: Introductionmentioning
confidence: 99%